PCR amplification of variable sequence upstream of katG gene to subdivide strains of Mycobacterium tuberculosis complex. - Goyal, M (1994)
PCR amplification of a species-specific 2-kb KpnI fragment of variable size located 10 kb upstream of the katG gene was used to subdivide 130 clinical isolates of Mycobacterium tuberculosis. Seven subtypes were identified, and their frequencies were distributed normally with respect to the size of the amplified product.